Investigation of Corrosion Mechanisms of Coated and Uncoated Magnesium Alloys - CHRISTOS KOUSIS (2022)
The corrosion-driven organic coating failure of Mg alloys and in particular the E717 alloy was investigated using a combination of in-situ Scanning Kelvin Probe (SKP) analysis and time-lapse photography where two principal failure mechanisms were identified: cathodic delamination and filiform corrosion. Initiation of underfilm corrosion by application of group I chloride salt to a coating defect produced a cathodic-driven coating delamination. The delamination distance increased linearly with time and the delamination occurred both in the presence and absence of oxygen. Post-corrosion elemental analysis of the delaminated regions using secondary-ion mass spectrometry revealed an abundance of group I cation, but no chloride. Experiments using the SKP and Stratmann-type Mg samples showed that the delamination rates remained linear even at protracted holding times and were insensitive to the type of group I cation present in the initiating electrolyte. Additional experiments on AZ31 and AZ91 Mg alloys revealed that both alloys are susceptible to organic coating delamination with the latter alloy being the most resistant to coating deadhesion. The mechanism was discussed in terms of anodic dissolution at the defect coupled predominantly with underfilm hydrogen evolution, producing organic coating disbondment under conditions where cations are able to transport ionic current within a region of increased pH. The second focus of this thesis was to study the filiform corrosion (FFC) of organic coated E717, AZ31 and AZ91 Mg alloys. The FFC was inoculated by applying MgCl2, HCl and FeCl2 in a coating defect and the FFC propagation rates were quantified by determining the underfilm corroded area with time, which were shown to increase as a function of log[Cl-], remain unaffected by the absence of oxygen, but strongly dependent on the relative humidity of the holding environment. SEM-EDX surface analysis of FFC affected regions was used in combination with in-situ SKP mapping to elucidate the mechanism of FFC propagation, where chloride-induced anodic dissolution at the disbondment front is coupled with the reduction of water on a cathodically activated corroded surface behind with progressive Cl- entrapment in the FFC tail. Finally, the localised corrosion behaviour of the E717 Mg alloy immersed in chloride-containing electrolytes was investigated using an in-situ Scanning Vibrating Electrode Technique (SVET) coupled with Time-lapse Imaging (TLI). The localised corrosion was characterised by discrete local anodes corresponding with the leading edges of dark filiform-like features that combine with time to produce a mobile anodic front leaving a cathodically activated corroded surface behind similar to what was observed with the FFC mechanism. Breakdown potential, measured using time-dependent free corrosion potential transients and potentiodynamic polarisation at neutral and high alkalinity respectively, were shown to vary with the log[Cl-] and the time for corrosion initiation was progressively decreased with increasing chloride concentration.